Minds on music : composition for creative and critical thinking - Kaschub, Michele, 1967- (Ebook Central Academic Complete Collection, 2009)
This textbook enhances preservice and practicing music educators' understanding of ways to successfully engage children in music composition. It offers both a rationale for the presence of composition in the music education program and a thorough review of what we know of children's compositional practices to date. Minds On Music offers a solid foundation for planning and implementing composition lessons with students in grades PreK-12.